Veganism and Oral Health—An Overview through the Perspective - Pandya, Visha Shailesh; Fiorillo, Luca; Kalpe, Sneha; Mehta, Vini; Meto, Aida; Certo, Agostino Di; Russo, Diana; Gorassini, Francesca; Mancini, Maura; Mancini, Alessandra; D'Amico, Cesare (European Journal of General Dentistry, 2023)
When meat and dairy products are no longer consumed, the practice of veganism, which forgoes the use of animal products, substantially impacts diet. The prevention and treatment of diseases like rheumatoid arthritis, diabetes, neurodegeneration, hypertension, and vascular diseases are usually aided by vegan diets. Vegan diets are associated with improved cardiovascular health and better nutrition quality than omnivorous diets. Vegans and vegetarians have a lower risk of periodontal disease but may be more prone to tooth erosion and dental caries due to deficiencies in vitamin B12 and lower saliva pH. A vegetarian or vegan diet may increase the risk of developing tooth erosion, but an omnivorous diet may increase the risk of periodontal disease and dental caries. Further clinical research must be performed to produce more statistically significant results and to support future studies that contrast omnivore, vegetarian, and vegan diets and their effects on dental health status.
Keywords: veganism; oral health; dental diseases; general health; vegetarianism